2020
DOI: 10.3389/fpsyg.2019.02933
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and Prayer on Teacher Stress and Burnout in an Italian Cohort: A Pilot, Before-After Controlled Study

Abstract: Introduction: Teaching is a stressful profession that exposes workers to the risk of burnout. Techniques involving higher mental functions, such as transcendental meditation and prayer, have been used in stress and burnout prevention programs. In this study, we report the results of an experience conducted in a group of teachers of a religious institute, in which prayer was used as a technique to prevent burnout. Methods: Fifty teachers and support staff employed at a Catholic school of a Congregation of nuns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 62 publications
4
56
0
1
Order By: Relevance
“…Concerning this, numerous studies highlighted the effectiveness of spirituality and religious activity as a coping strategy for the empowerment of mental health (e.g., life satisfaction, happiness, optimism) and the management of stress-related events across the adult life span (e.g., Chirico, 2017;Frankel & Hewitt, 1994;Lawler-Row & Elliott, 2009). There is evidence that interventions based on the use of meditational techniques and prayer can be very effective in reducing emotional exhaustion and enhancing mental health (e.g., reducing depressive symptoms, anxiety) in adults (Chirico et al, 2020), especially in older individuals who have to deal with different types of stressful events (e.g., loss of relatives, occurrence of chronic diseases) threatening their mental health. In this regard, spirituality-based interventions are effective in reducing depression and anxiety and empowering optimism among older individuals (Rajagopal et al, 2002), even among those exhibiting cardiovascular diseases (Ai et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning this, numerous studies highlighted the effectiveness of spirituality and religious activity as a coping strategy for the empowerment of mental health (e.g., life satisfaction, happiness, optimism) and the management of stress-related events across the adult life span (e.g., Chirico, 2017;Frankel & Hewitt, 1994;Lawler-Row & Elliott, 2009). There is evidence that interventions based on the use of meditational techniques and prayer can be very effective in reducing emotional exhaustion and enhancing mental health (e.g., reducing depressive symptoms, anxiety) in adults (Chirico et al, 2020), especially in older individuals who have to deal with different types of stressful events (e.g., loss of relatives, occurrence of chronic diseases) threatening their mental health. In this regard, spirituality-based interventions are effective in reducing depression and anxiety and empowering optimism among older individuals (Rajagopal et al, 2002), even among those exhibiting cardiovascular diseases (Ai et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Our research revealed that lack of time for meditation was strongly associated with stress. It is well known that meditation can significantly increase workers’ resilience [ 52 ], and meditative prayer has been used to prevent burnout in workers [ 53 ]. Mindfulness techniques have been used to support HCWs struggling with COVID-19 [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our research revealed that lack of time for meditation was strongly associated with stress. It is well known that meditation can significantly increase workers' resilience [29] and meditative prayer has been used to prevent burnout in workers [30]. Mindfulness techniques have been used to support HCWs struggling with COVID-19 [31].…”
Section: Discussionmentioning
confidence: 99%